Peningkatan Kompetensi Keimanan Melalui Problem Based Learning Pada Materi Rasul-Rasul Allah di Kelas IV SDN 13 Tanjung Beringin - Suzana, Yan (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Islamic Religious Education plays an important role in shaping the character and morals of students. One of the key topics taught is belief in the Messengers of Allah. However, in practice, students’ understanding of this topic remains low, particularly in class IV of SDN 13 Tanjung Beringin, as evidenced by the lack of enthusiasm and student involvement in learning. One of the causes is the monotonous teaching method. To address this issue, this research aims to improve students' understanding by implementing the Problem Based Learning (PBL) model. The study was conducted with grade IV students at SDN 13 Tanjung Beringin, focusing on the topic of belief in the Messengers of Allah. The expected outcome is an improvement in students' understanding of the material, increased student engagement, and the application of religious values in daily life. This research uses a classroom action research approach to analyze students’ learning outcomes, active participation, and the application of religious values in their behavior.